High-temperature-resistant halogen-free flame-retardant cable material for nuclear power station cable and preparation method thereof

By combining sericite and iron oxide as an infrared shielding agent with a halogen-free flame retardant system of active magnesium hydroxide and bismuth hydroxide, the problems of high cost and antioxidant migration in nuclear power plant cable materials have been solved, achieving high-efficiency high-temperature resistance and long service life, meeting the stringent requirements of nuclear power plant cables.

CN121005980APending Publication Date: 2025-11-25SHANGDONG HUALING CABLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511439323.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing nuclear power plant cable materials suffer from high costs, complex processes, and the tendency for antioxidants to migrate and leach out, affecting material performance and safety, in order to achieve high temperature resistance and long service life.

Method used

Sericite and iron oxide are used as infrared shielding agents, and active magnesium hydroxide and bismuth hydroxide are combined to form a halogen-free flame retardant system. The material properties are improved through hydrothermal modification and surface activation treatment, reducing the amount of antioxidant and avoiding migration and precipitation.

Benefits of technology

It significantly reduces the cost of antioxidants, improves the material's high-temperature resistance, halogen-free properties, low smoke, and low toxicity, meeting the requirements of nuclear power plants, and simplifies the production process, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a high-temperature-resistant halogen-free flame-retardant cable material for a nuclear power station cable and a preparation method thereof. The cable material is prepared from the following components in parts by mass: 50 parts of ethylene-vinyl acetate copolymer, 20 parts of ethylene propylene diene monomer, 20 parts of ethylene-octylene copolymer, 10 parts of maleic anhydride grafted ethylene-octylene copolymer, 3 to 6 parts of silicone master batch, 2 to 4 parts of carbon black master batch, 180 to 220 parts of active magnesium hydroxide, 40 to 60 parts of bismuth hydroxide, 8 to 16 parts of sericite and 4 to 8 parts of ferric oxide. The composition comprises the following components in parts by weight: 1-3 parts of a main antioxidant, 0.5-1.5 parts of an auxiliary antioxidant, 2-4 parts of TAIC and 3-6 parts of octaphenylcyclotetrasiloxane. The cable material prepared by the invention shows excellent high temperature resistance, long service life and flame retardance, the preparation process is simple and easy to operate, the production cost is low, the productivity is stable, and the production requirements of nuclear power station cables are met.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer materials, in particular to a high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plants and a preparation method thereof. BACKGROUND

[0002] Due to the special use environment of nuclear power plants, the operating equipment has high requirements. The cable for nuclear power plants must have excellent properties such as low smoke, halogen-free, flame-retardant, radiation-resistant, and high-temperature-resistant on the basis of general electrical properties and mechanical properties of ordinary cables. The existing nuclear power plant cables have significant bottlenecks in the technical path. In order to achieve the high-temperature-resistant and long-life properties of the cable, the industry generally relies on a large amount of high-temperature-resistant antioxidant. The purity and market unit price of such antioxidant are higher than those of ordinary antioxidants, and the addition amount is relatively high. Only the cost of antioxidant accounts for 15%-20% of the total cost of cable material raw materials. More importantly, high-dose antioxidants are prone to "migration and precipitation" during processing, which not only causes the material surface to appear frost phenomenon, affecting the adhesion with the insulation layer, but also may reduce the volume resistivity of the cable material, posing a safety hazard. SUMMARY

[0003] In view of the problems of high cost, complex process, and insufficient comprehensive performance of the existing high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plants, a high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plants and a preparation method thereof are provided. The present application uses sericite and iron oxide as a compound infrared shielding agent, which can significantly improve the comprehensive performance of the cable material when combined with a small amount of antioxidant.

[0004] The technical scheme adopted by the present application is as follows: The present application aims to provide a high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plants, which comprises the following components in parts by mass: ethylene-vinyl acetate copolymer 50 parts, ethylene-propylene-diene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone masterbatch 3-6 parts, carbon black masterbatch 2-4 parts, active magnesium hydroxide 180-220 parts, bismuth hydroxide 40-60 parts, sericite 8-16 parts, iron oxide 4-8 parts, main antioxidant 1-3 parts, auxiliary antioxidant 0.5-1.5 parts, TAIC 2-4 parts, and octaphenylcyclotetrasiloxane 3-6 parts.

[0005] Further, the present application comprises the following components in parts by mass: ethylene-vinyl acetate copolymer 50 parts, ethylene-propylene-diene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone masterbatch 5 parts, carbon black masterbatch 3 parts, active magnesium hydroxide 200 parts, bismuth hydroxide 55 parts, sericite 12 parts, iron oxide 6 parts, main antioxidant 2 parts, auxiliary antioxidant 1 part, TAIC 3 parts, and octaphenylcyclotetrasiloxane 4 parts.

[0006] Further, the vinyl acetate content in the ethylene-vinyl acetate copolymer is ≥33%.

[0007] Further, the preparation method of the active magnesium hydroxide is: (1) precursor preparation: prepare a magnesium sulfate aqueous solution with a concentration of 1.2 mol / L, stir (speed 300-400 r / min) in a constant temperature water bath of 50-60℃, slowly add a 2.0 mol / L sodium hydroxide aqueous solution (addition speed 10-15 mL / min), control the pH value at 10.5-11.0, and react to generate magnesium hydroxide precipitate, and keep stirring for 30 min to form a uniform magnesium hydroxide suspension; (2) hydrothermal modification: transfer the suspension to a high-pressure reaction kettle, heat to 120-130℃, keep the pressure at 0.3-0.4 MPa, and hydrothermally react for 2.5-3 h, then naturally cool to 80℃, filter to obtain a magnesium hydroxide filter cake, wash with deionized water until the filtrate pH=7-8, and remove residual sodium salt; (3) surface activation treatment: place the filter cake in a vacuum drying oven, dry at 80-90℃ for 4-5 h, crush to a particle size of 1-5 μm; add the crushed magnesium hydroxide in a high-speed mixer (speed 1500-2000 r / min), heat to 80-90℃; add silane coupling agent KH-570 twice (interval 10 min), continue stirring for 40-50 min, and finally add polyethylene glycol 400 and stir for 20 min; cool to room temperature, pass through a 200 mesh sieve, and obtain active magnesium hydroxide.

[0008] Further, the amount of silane coupling agent KH-570 is 1.5%-2.0% of the mass of magnesium hydroxide; and the amount of polyethylene glycol 400 is 0.8%-1.2% of the mass of magnesium hydroxide.

[0009] Further, the main antioxidant is a mixture of antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:2.

[0010] Further, the auxiliary antioxidant is antioxidant 168.

[0011] Further, the carbon black masterbatch is a mixture of N330 carbon black and polyethylene wax in a mass ratio of 2-3:0.5-1.5.

[0012] The second object of the present application is to provide a preparation method of a high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plant cables, comprising the following steps: Step one: weigh each component raw material according to the formula proportion; Step two: melt and mix the raw materials in a temperature of 140-160℃ for 10-20 min; Step three: melt the material obtained in step two and add it into a double screw extruder, extrude and granulate at a temperature of 160-180℃, air cool to room temperature, to obtain the cable material.

[0013] Compared with the prior art, the nuclear power plant cable resistant to radiation and prepared from the halogen-free flame-retardant cable material and the preparation method thereof have the following advantages: (1) The sericite and iron oxide are used as the infrared shielding agent in the present application, and the two form a synergistic effect: the layered structure of the sericite can reflect infrared rays and reduce the accumulation of heat in the material; the iron oxide can selectively absorb infrared band energy, further reducing the thermal load of the material. The system can significantly reduce the amount of antioxidant required, compared with the traditional formula, the cost of the antioxidant is reduced, and the problem of “migration and precipitation” of high-dose antioxidants is avoided; (2) The active magnesium hydroxide prepared by hydrothermal modification and surface activation greatly improves the compatibility of the active magnesium hydroxide with the resin matrix, avoiding the mechanical property decline caused by uneven dispersion of traditional inorganic flame retardants; the halogen-free flame-retardant system is formed by matching bismuth hydroxide, and the two can synergistically decompose at high temperatures: the magnesium hydroxide releases crystal water to reduce the temperature, and the bismuth hydroxide forms a bismuth glassy protective layer to isolate oxygen, so that the material finally meets the strict requirements of nuclear power plants in terms of halogen-free, low smoke and low toxicity; (3) The preparation process of the present application is simple and easy to operate, does not require complex equipment or special process, and the raw materials are all industrialized and easily available products, which can be directly adapted to the existing cable material production line, with low production cost and stable production capacity, meeting the demand of large-scale production of nuclear power plant cables. DETAILED DESCRIPTION

[0014] The present application is further described below through the description of specific embodiments, but this is not a limitation on the present application. Those skilled in the art can make various modifications or improvements according to the basic idea of the present application, as long as they do not deviate from the basic idea of the present application, and they are within the protection scope of the present application.

[0015] In the following examples and comparative examples, the methods used, unless otherwise specified, are prior art; reagents not specifically mentioned are conventional reagents, which can be purchased from conventional reagent production and sales companies, and some raw material production companies or CAS numbers are as follows: Ethylene-vinyl acetate copolymer, CAS number 24937-78-8; Ethylene-vinyl acetate copolymer, CAS number 24937-78-8; Ethylene-vinyl acetate copolymer, CAS number 24937-78-8; Ethylene-vinyl acetate copolymer, CAS number 24937-78-8; Silicone master batch, purchased from Chengdu Silike Technology Co., Ltd.;‌ N330 carbon black, purchased from Shandong Casone New Material Co., Ltd.; Polyethylene wax, purchased from Qingdao Sainuo New Material Co., Ltd.; Bismuth hydroxide, CAS No. 10361-43-0, purchased from Shandong Jinshengtai Chemical Co., Ltd.; Sericit, specification: 400 mesh, purchased from Chuzhou Baota Sericit Mining Co., Ltd.; Iron oxide, purchased from Zibo Baoyan Chemical Co., Ltd.; TAIC, CAS No. 1025-15-6, purchased from Shanghai Dunmei New Material Technology Co., Ltd.; Octaphenylcyclotetrasiloxane, CAS No. 546-56-5, purchased from Jinan Wolde Chemical Co., Ltd.; Antioxidant 1010, CAS No. 6683-19-8; Antioxidant 1076, CAS No. 2082-79-3; Antioxidant 168, CAS No. 31570-04-4.

[0016] Example 1 A kind of nuclear power cable for high temperature resistant halogen-free flame retardant cable material, by mass fraction includes the following components (100 g / portion): ethylene-vinyl acetate copolymer 50 parts, ethylene-propylene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone master batch 3 parts, carbon black master batch 4 parts, active magnesium hydroxide 180 parts, bismuth hydroxide 40 parts, sericit 8 parts, iron oxide 4 parts, main antioxidant 1 part, auxiliary antioxidant (antioxidant 168) 0.5 parts, TAIC 2 parts, octaphenylcyclotetrasiloxane 3 parts.

[0017] Among them, the carbon black master batch is mixed by N330 carbon black and polyethylene wax according to the mass ratio of 2:1.5; the main antioxidant is mixed by antioxidant 1010 and antioxidant 1076 according to the mass ratio of 3:2; The specific preparation steps of the cable material are as follows: Step one: weigh each component raw material according to the formula proportion; Step two: melt and mix the raw materials in a temperature of 140 DEG C for 10 min; Step three: melt the material obtained in step two into a double screw extruder, extrude and granulate under the condition of temperature 160 DEG C, air cooling to room temperature, to obtain the cable material.

[0018] Among them, the preparation method of active magnesium hydroxide is as follows: (1) Precursor preparation: prepare a magnesium sulfate aqueous solution with a concentration of 1.2 mol / L, stir (speed 300 r / min) in a 50℃ constant temperature water bath, slowly add 2.0 mol / L sodium hydroxide aqueous solution (addition speed 10 mL / min), control the pH value at 10.5-11.0, and react to generate magnesium hydroxide precipitate, keep stirring for 30 min, and form a uniform magnesium hydroxide suspension; (2) Hydrothermal modification: transfer the suspension to a high-pressure reaction kettle, heat to 120℃, maintain a pressure of 0.3-0.4 MPa, and hydrothermally react for 2.5 h. After the reaction is completed, naturally cool to 80℃, filter to obtain a magnesium hydroxide filter cake, wash with deionized water until the filtrate pH = 7-8, and remove residual sodium salt; (3) Surface activation treatment: place the filter cake in a vacuum drying oven, dry at 80℃ for 4 h, crush to a particle size of 1-5 μm; add the crushed magnesium hydroxide to a high-speed mixer (speed 1500 r / min), heat to 80-90℃; add silane coupling agent KH-570 (the amount of silane coupling agent KH-570 is 1.5% of the mass of magnesium hydroxide) in two portions, with an interval of 10 min, continue to stir for 40-50 min, finally add polyethylene glycol 400 (the amount of polyethylene glycol 400 is 1.2% of the mass of magnesium hydroxide), and stir for 20 min; cool to room temperature, pass through a 200 mesh sieve, and obtain active magnesium hydroxide.

[0019] Example 2 A high-temperature-resistant halogen-free flame-retardant cable material for nuclear power plant cables, comprising the following components (300 g / portion) by mass fraction: ethylene-vinyl acetate copolymer 50 parts, ethylene-propylene-diene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone masterbatch 6 parts, carbon black masterbatch 2 parts, active magnesium hydroxide 220 parts, bismuth hydroxide 60 parts, sericite 16 parts, iron oxide 8 parts, primary antioxidant 3 parts, auxiliary antioxidant (antioxidant 168) 1.5 parts, TAIC 4 parts, and octaphenylcyclotetrasiloxane 6 parts.

[0020] Among them, the carbon black masterbatch is a mixture of N330 carbon black and polyethylene wax in a mass ratio of 3:0.5; the primary antioxidant is a mixture of antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:2; The specific preparation steps of the cable material are as follows: Step one: weigh each component raw material according to the formula proportion; Step two: add each raw material to a temperature of 160℃ in a banbury mixer and melt mix for 20 min; Step three: add the melt material obtained in step two to a twin-screw extruder, extrude and granulate under the condition of a temperature of 180℃, air cool to room temperature, and obtain the cable material.

[0021] The preparation method of the active magnesium hydroxide is as follows: (1) Preparation of precursor: prepare a magnesium sulfate aqueous solution with a concentration of 1.2 mol / L, stir (speed 400 r / min) in a 60°C constant temperature water bath, slowly add 2.0 mol / L sodium hydroxide aqueous solution (addition speed 15 mL / min), control the pH value at 10.5-11.0, and react to generate magnesium hydroxide precipitate, and keep stirring for 30 min to form a uniform magnesium hydroxide suspension; (2) Hydrothermal modification: transfer the suspension to a high-pressure reaction kettle, heat to 130°C, keep the pressure at 0.3-0.4 MPa, and hydrothermally react for 3 h, then naturally cool to 80°C, filter to obtain a magnesium hydroxide filter cake, wash with deionized water until the filtrate pH is 7-8, and remove residual sodium salt; (3) Surface activation treatment: place the filter cake in a vacuum drying oven, dry at 90°C for 5 h, crush to a particle size of 1-5 μm, add the crushed magnesium hydroxide into a high-speed mixer (speed 2000 r / min), heat to 80-90°C, add silane coupling agent KH-570 (the amount of silane coupling agent KH-570 is 2.0% of the mass of magnesium hydroxide) in two portions with an interval of 10 min, continue to stir for 40-50 min, finally add polyethylene glycol 400 (the amount of polyethylene glycol 400 is 0.8% of the mass of magnesium hydroxide), and stir for 20 min; cool to room temperature, pass through a 200 mesh sieve, and obtain the active magnesium hydroxide.

[0022] Example 3 A kind of nuclear power station cable for high temperature resistant halogen-free flame retardant cable material, by mass fraction includes the following components (500 g / portion): ethylene-vinyl acetate copolymer 50 parts, ethylene-propylene-diene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone masterbatch 5 parts, carbon black masterbatch 3 parts, active magnesium hydroxide 200 parts, bismuth hydroxide 55 parts, sericite 12 parts, iron oxide 6 parts, main antioxidant 3 parts, auxiliary antioxidant (antioxidant 168) 1 part, TAIC 3 parts, octaphenylcyclo tetrasiloxane 4 parts.

[0023] Among them, the carbon black masterbatch is made by mixing N330 carbon black and polyethylene wax in a mass ratio of 2:1; the main antioxidant is made by mixing antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:2; The specific preparation steps of the cable material are as follows: Step one: weigh each component raw material according to the formula proportion; Step two: add each raw material into a temperature of 150°C mixing mill for melt mixing for 15 min; Step three: add the melt material obtained in step two into a twin-screw extruder, extrude and granulate under the condition of temperature 170°C, air cool to room temperature, and obtain the cable material.

[0024] The preparation method of the active magnesium hydroxide is as follows: (1) Preparation of precursor: prepare a magnesium sulfate aqueous solution with a concentration of 1.2 mol / L, stir (speed 300 r / min) in a 55°C constant temperature water bath, slowly add a 2.0 mol / L sodium hydroxide aqueous solution (addition speed 15 mL / min), control the pH value to be 10.5-11.0, and generate magnesium hydroxide precipitate by reaction, and keep stirring for 30 min to form a uniform magnesium hydroxide suspension; (2) Hydrothermal modification: transfer the suspension to a high-pressure reaction kettle, heat to 120°C, keep the pressure at 0.3 MPa, and hydrothermally react for 2.5 h, then naturally cool to 80°C, filter to obtain a magnesium hydroxide filter cake, wash with deionized water until the pH of the filtrate is 7-8, and remove residual sodium salt; (3) Surface activation treatment: place the filter cake in a vacuum drying box, dry at 88°C for 5 h, crush to a particle size of 1-5 μm, add the crushed magnesium hydroxide in a high-speed mixer (speed 1800 r / min), heat to 90°C, add silane coupling agent KH-570 (the amount of silane coupling agent KH-570 is 1.8% of the mass of the magnesium hydroxide) in two portions with an interval of 10 min, continue to stir for 45 min, finally add polyethylene glycol 400 (the amount of polyethylene glycol 400 is 1% of the mass of the magnesium hydroxide), and stir for 20 min; cool to room temperature, pass through a 200-mesh sieve, and obtain the active magnesium hydroxide.

[0025] Comparative Example 1 The difference from Example 3 is that the active magnesium hydroxide is replaced by ordinary industrial-grade magnesium hydroxide (not surface-activated, particle size 5-10 μm), and the amount of raw materials is unchanged; the other steps and preparation processes are the same as those of Example 3.

[0026] Comparative Example 2 The difference from Example 3 is that the sericite and iron oxide in the raw materials are removed, and the other steps and preparation processes are the same as those of Example 3.

[0027] Comparative Example 3 The difference from Example 3 is that the primary antioxidant is replaced by a single antioxidant 1010, and the amount of antioxidant 1010 is unchanged; the other steps and preparation processes are the same as those of Example 3.

[0028] Comparative Example 4 The difference from Example 3 is that the active magnesium hydroxide is replaced by decabromodiphenyl ether, and the bismuth hydroxide is replaced by antimony trioxide, and the amount of raw materials is unchanged; the other steps and preparation processes are the same as those of Example 3.

[0029] Test Example: Performance Test 1. Test material: high-temperature-resistant halogen-free flame-retardant cable material prepared in the examples and comparative examples of the present application.

[0030] 2. Test method: (1) High temperature resistance test: including mechanical property retention rate after 135℃ heat aging (the specific detection method refers to GB / T1040.3-2006, GB / T7141-2021) and heat distortion temperature detection (the specific detection method refers to GB / T1634.2-2021); (2) Long life performance test: 120℃ accelerated heat aging life calculation (the specific detection method refers to GB / T7141-2021); (3) Flame retardant performance test: oxygen index detection (the specific detection method refers to GB / T 2406.2-2009), vertical burning grade (UL94) detection (the specific detection method refers to GB / T 18380.12-2022); (4) Combustion smoke density detection (the specific detection method refers to GB / T 8323.2-2020), halogen acid gas release amount detection (the specific detection method refers to GB / T 17650.2-1998).

[0031] 3. Test results, as shown in Table 1.

[0032] Table 1 Performance test results of cable materials obtained by examples and comparative examples Test item Unit Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength retention rate after heat aging at 135°C % 86.5 89.2 90.2 72.5 68.3 75.1 88.7 Heat deflection temperature (HDT) ℃ 128.3 130.1 132.5 115.7 129.8 128.5 131.2 Predicted life at 90°C Years 82 85 88 52 45 58 70 Limiting oxygen index (LOI) % 31.2 32.5 33.8 28.3 32.2 32.4 33.2 Vertical burning rating (UL94) - V-0 V-0 V-0 V-1 V-0 V-0 V-0 Bunched flame-retardant char length m 2.1 1.8 1.6 2.6 1.9 1.8 1.5 Minimum light transmittance during combustion % 62.5 65.3 67.8 60.2 64.7 65.0 32.6 Halogen acid gas release amount mg / g 0.07 0.08 0.09 0.09 0.08 0.08 2.15 As shown in Table 1, the performance test results of the halogen-free flame-retardant cable material with high temperature resistance obtained by the examples of the present application are all good, showing excellent high temperature resistance, flame retardant performance and long service life; while the performance of each group of comparative examples is affected to different degrees.

[0033] The above examples only illustrate the principles and effects of the present application, and are not used to limit the present application. Any person skilled in the art can modify or change the above examples without departing from the spirit and scope of the present application. Therefore, all equivalent modifications or changes made by those skilled in the art without departing from the spirit and technical idea disclosed by the present application should be covered by the claims of the present application.

Claims

1. A high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables, characterized in that, The following components are included by mass fraction: ethylene-vinyl acetate copolymer 50 parts, ternary ethylene-propylene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone master batch 3-6 parts, carbon black master batch 2-4 parts, active magnesium hydroxide 180-220 parts, bismuth hydroxide 40-60 parts, sericite 8-16 parts, iron oxide 4-8 parts, primary antioxidant 1-3 parts, auxiliary antioxidant 0.5-1.5 parts, TAIC 2-4 parts, octaphenylcyclotetrasiloxane 3-6 parts. ​ 2. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, characterized in that, The following components are included by mass fraction: ethylene-vinyl acetate copolymer 50 parts, ternary ethylene-propylene rubber 20 parts, ethylene-octene copolymer 20 parts, maleic anhydride grafted ethylene-octene copolymer 10 parts, silicone master batch 5 parts, carbon black master batch 3 parts, active magnesium hydroxide 200 parts, bismuth hydroxide 55 parts, sericite 12 parts, iron oxide 6 parts, primary antioxidant 2 parts, auxiliary antioxidant 1 part, TAIC 3 parts, octaphenylcyclotetrasiloxane 4 parts.

3. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, characterized in that, The content of vinyl acetate in the ethylene-vinyl acetate copolymer is ≥33%.

4. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, wherein, The preparation method of the active magnesium hydroxide is: ​ (1) Preparation of precursor: prepare a magnesium sulfate aqueous solution with a concentration of 1.2 mol / L, stir in a 50-60℃ constant temperature water bath, slowly add 2.0 mol / L sodium hydroxide aqueous solution, control the pH value at 10.5-11.0, and react to generate magnesium hydroxide precipitate, keep stirring for 30 min to form a uniform magnesium hydroxide suspension; (2) Hydrothermal modification: transfer the suspension to a high-pressure reaction kettle, heat to 120-130℃, maintain a pressure of 0.3-0.4 MPa, and hydrothermally react for 2.5-3 h, then naturally cool to 80℃, filter to obtain magnesium hydroxide filter cake, wash with deionized water until the filtrate pH=7-8, and remove residual sodium salt; (3) Surface activation treatment: place the filter cake in a vacuum drying oven, dry at 80-90℃ for 4-5 h, crush to a particle size of 1-5 μm, add the crushed magnesium hydroxide in a high-speed mixer, heat to 80-90℃, add silane coupling agent KH-570 in two portions, continue stirring for 40-50 min, and finally add polyethylene glycol 400 and stir for 20 min; cool to room temperature, pass through a 200 mesh sieve, and obtain active magnesium hydroxide.

5. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, wherein, The amount of silane coupling agent KH-570 is 1.5%-2.0% of the mass of magnesium hydroxide; the amount of polyethylene glycol 400 is 0.8%-1.2% of the mass of magnesium hydroxide. ​ 6. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, wherein, The primary antioxidant is a mixture of antioxidant 1010 and antioxidant 1076 in a mass ratio of 3:

2.

7. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, wherein, The auxiliary antioxidant is antioxidant 168. ​ 8. The high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to claim 1, wherein, The carbon black master batch is a mixture of N330 carbon black and polyethylene wax in a mass ratio of 2-3:0.5-1.

5.

9. A process for the preparation of a high temperature resistant, halogen-free, flame retardant cable compound for nuclear power plant cables according to any one of claims 1 to 8, characterized in that The following steps are included: Step one: weigh each component raw material according to the formula proportion; Step two: add each raw material to a banbury mixer with a temperature of 140-160℃ and melt mix for 10-20 min; Step three: melt the material obtained in step two and add into a twin-screw extruder, extrude and granulate at a temperature of 160-180°C, air-cool to room temperature, to obtain the cable material.